Safeguarding Public Health Through Iot-Based Real-Time Water Monitoring At A River Intake Zone - Zubaidah, Tien; Hamzani, Sulaiman; Masmitra, Kresna Dinta; Legowo, Agung Cahyo (State Islamic University of Sunan Ampel, 2025)
Access to safe and clean water is essential to human health, yet many river systems in Indonesia remain vulnerable to pollution from domestic, agricultural, and industrial sources. Inadequate water quality monitoring near raw water intakes may increase the risk of waterborne diseases, especially in tropical regions. This study introduces a low-cost, real-time Internet of Things (IoT)-based monitoring system designed to safeguard public health by improving early detection of potential contamination at a key water intake along the Martapura River. The system utilized an Arduino Mega microcontroller integrated with temperature, pH, and turbidity sensors. Data were transmitted every five minutes via an ESP32 Wi-Fi module to the ThingSpeak cloud platform and visualized through a mobile dashboard accessible to water utility managers. Field testing was conducted upstream and downstream of the PTAM Intan Banjar intake in South Kalimantan. The system demonstrated strong agreement with laboratory reference measurements (Pearson's r > 0.99) and maintained 98.7% data transmission reliability. It operated continuously for over 23 hours per charge, offering a resilient and portable tool for real-time environmental surveillance. This affordable and user-friendly IoT system enables timely water quality monitoring and supports preventive public health actions in response to contamination risks.